Discussion on a computation-oriented network modality——computing power network modality - Rui LIN; Wenjuan XING; Bo LEI (Dianxin kexue)
New computing applications present new challenges to communication networks, for example, traditional network cannot meet the demands of flexible deployment, customized services, security and trustworthiness of new services.As a development paradigm that separated network technology and supported environment, polymorphic network provided new solutions to support the differentiated demands of various new applications.A type of computation-oriented network modality namely computing power network modality was discussed, for the computation-oriented business requirements based on the development trend of computing power network.Firstly, the design of computing power network modality was investigated, then the key technologies of computing power network modality were analyzed.Finally, the application scenarios of computing power network were prospected.It is hoped that the discussion can provide a reference for the future research and development on application of computation-oriented polymorphic network.